Implementasi Building Information Modelling (BIM) 5D Pada Estimasi Volume dan Biaya Pekerjaan Struktur - Adi Prastya, Celvin; Hendriyani, Irna; Pratiwi, Reno (BANDAR: JOURNAL OF CIVIL ENGINEERING, 2025)
The objective of this study is to evaluate the outcomes of cost estimation calculations conducted through the manual approach versus the Building Information Modelling (BIM) approach. BIM addresses the limitations of conventional software like AutoCAD and Microsoft Excel, which are 2D-based and complicate coordination among different engineering fields. BIM, through the integration of 3D (modeling), 4D (scheduling), 5D (cost), 6D (sustainability), and 7D (operation and maintenance), offers a comprehensive framework for project planning, management, and evaluation. This study analyzes the efficiency of volume and cost estimation in the construction of the Balikpapan’s DP3 and DISDAG Building project in the city of Balikpapan using the BIM 5D concept with Autodesk Revit 2022 software. The research results indicate that volume and cost estimations with BIM 5D are more efficient compared to conventional methods. The concrete work volume with BIM is compared to that of conventional methods from the consultant, there is a saving of 4.92% for concrete works, and 5.16% of saving for rebar works. These findings demonstrate that the implementation of BIM 5D in Autodesk Revit is lower and more efficient in volume and cost estimation.